The role of GRP78/ATF6/IRE1 and caspase-3/Bax/Bcl2 signaling pathways in the protective effects of gallic acid against cadmium-induced liver damage in rats. - Yildirim, Serkan; Cinar, Irfan; Gelen, Volkan; Sengul, Emin (Mashhad University of Medical Sciences, 2023)
Cadmium (CD) causes widespread and severe toxic effects on various tissues. Studies have shown that apoptosis, inflammation, and endoplasmic reticulum stress play a role in organ damage caused by CD. Phenolic compounds with strong antioxidant effects are found in various fruits and vegetables. One of these compounds is Gallic acid (GA), which is found both free and hydrolyzable in grapes, pomegranate, tea, hops, and oak bark. Result of various studies show that GA has active antioxidant, anti-inflammatory, and anti-apoptotic properties. In our study, we investigated the mechanism of the protective effect of GA on CD-induced hepatotoxicity in rats.In this study, 50 adult male Sprague Dawley rats weighing approximately 200-250 g were used and the rats were divided into 5 groups: Control, CD, GA50+CD, GA100+CD, and GA100. The rats were treated with GA (50 and 100 mg/kg body weight), and Cd (6.5 mg/kg) was administrated to the rats for 5 consecutive days. The liver enzymes, TB levels in serum samples, oxidative stress, inflammation, ER stresses, apoptosis marker, histopathology, 8-OHDG, and caspase-3 positivity were analyzed.CD administration significantly increased liver enzyme levels (AST, ALT, ALP, and LDH), MDA, IL-1-β, IFN-γ, TNF-α, IL-10, IL-6, GRP78, CHOP, ATF6, p -IRE1, sXBP, Bax mRNA expression, Caspase 3, and 8-OHdG expression (P<0.05). These values were found to be significantly lower in the Control, GA100+CD, and GA100 groups compared to the CD group (P<0.05). CD administration significantly decreased the expression levels of TB, IL-4, SOD, GSH, CAT, GPX, and Bcl-2 mRNA (P<0.05). These values were found to be significantly higher in the Control, GA100+CD, and GA100 groups compared to the CD group (P<0.05).The results of the present study indicated that GA prevented Cd-induced hepatic oxidative stress, inflammation, ER stress, apoptosis, and tissue damage in rats.
Keywords: hepatotoxicity; cadmium; inflammation; apoptosis; R; Medicine; Original Article; gallic acid; endoplasmic reticulum - stress; 3. Good health